DESCRIPTION OF THE QUALITY OF PHARMACY STUDENT SLEEP IN THE PANDEMIC PERIOD OF CORONA VIRUS DISEASE (COVID-19) - Rizky Nur Azmi; Deasy Nur Chairin Hanifa; Nur Sholeh Ariyodi Fernando; Maulina Rahmawati Putri (Universitas Muhammadiyah Kalimantan Timur, 2021)
Sleep is one of the basic human needs that important to support health. The existence of problems in the sleep phase can be the cause of various medical and psychological conditions. The existence of policy to online learning in Covid-19 pandemic can be one of the factors that can affect the quality of student sleep. This research aims to describe of the sleep quality description of pharmacy students during the pandemic. This research is use the Pittsburgh Sleep Quality Index (PSQI) questionnaire to assessment sleep quality of pharmacy student at the Universitas Muhammadiyah Kalimantan Timur from July to August 2020 and It was obtained as 140 respondents. The PSQI has seven components related to sleep habits including sleep duration, sleep disturbance, sleep latency time, sleep efficiency habits, daytime dysfunction, use of sleeping pills, and overall sleep quality. This research shown that 84.3% respondents is female sex. 42.1% of respondents needed more than 30 minutes to fall asleep. 81% of pharmacy students were classified in the poor sleepers group based on the PSQI scoring results. This shows that most pharmacy students had poor sleep quality during the Covid-19 pandemic.